PSYCHOEDUCATION REDUCES ANXIETY IN ELDERLY WITH HYPERTENSION IN NAMBAKOR VILLAGE SARONGGI DISTRICT SUMENEP - Suprayitno, Emdat; Yasin, Zakiyah; Karamah, Istiqamatul; Puspitasari, Dian Ika (Journal of Vocational Nursing, 2021)
Introduction: The problems in hypertension will cause emotional or mental disorders, one of which is anxiety. Feelings arise due to the fear and ignorance of an individual about hypertension experienced and the impact that will occur in the future. Psychoeducation is the provision of information about disease management and individual psychological aspects. This study aims to determine the effect of psychoeducation on the anxiety level of elderly patients with hypertension in Nambakor Village, Saronggi District.Methods: This research method is pre-experimental with the research design is one group pre test post test. The sampling technique used is Random Sampling and the number of samples is 30 respondents. Data collection using a questionnaire on the level of anxiety Depression Anxiety and Stress Scale.Result: The results showed that the mean of the anxiety score before the psychoeducation intervention was 24,43±7,60 and the mean of the anxiety score after the psychoeducation intervention was was 23,23 ± 7,83. The results of the paired t test of anxiety score was p = 0.002, means that there is significant difference in anxiety scores before and after psychoeducation.Conclusion: There is an influence of psychoeducation on the level of anxiety in the elderly with hypertension. The conclusion obtained is that psychoeducation can increase knowledge in patients with hypertension so that it is expected to be one form of intervention that can be applied.